Korelasi antara Kadar Asam Urat Tinggi dengan Tingkat Keparahan Preeklamsia: Menjelajahi Hubungan Antara Hiperurisemia dan Tingkat Keparahan Preeklamsia: Perspektif Klinis - I Wayan Artana Putra; Endang Sri Widiyanti; Amanda Sherman (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction: Preeclampsia is a pregnancy complication marked by hypertension and multi-organ dysfunction, contributing to significant maternal and fetal morbidity and mortality, particularly in developing nations. Identifying severe cases early remains challenging due to limited biomarker specificity and predictive accuracy. Uric acid has been proposed as a potential marker, though its reliability in predicting severity remains debated. Methods: This cross-sectional study included 54 pregnant women diagnosed with preeclampsia at RSUP Prof. Dr. I.G.N.G Ngoerah, Denpasar, with a gestational age of over 20 weeks. Participants were selected through consecutive sampling. Data on serum uric acid, blood pressure, proteinuria, and creatinine levels were analyzed using parametric statistical tests to assess correlations with preeclampsia severity. Results: Elevated uric acid levels (>6 mg/dL) were significantly associated with severe preeclampsia (p=0.039), with a prevalence ratio of 2.96. Strong correlations were found between uric acid and blood pressure (r=0.71, p=0.012) and proteinuria (r=0.64, p=0.012), while a moderate correlation existed with serum creatinine (r=0.40, p=0.002). Conclusion: Serum uric acid levels can be a useful indicator for assessing preeclampsia severity. However, its predictive value should be combined with other clinical and biochemical markers to enhance early detection and management strategies